Developing Experimental Scenarios to Evaluate Dynamic Response Effectiveness of DFIG-Based Wind Power Generator - Minh Khoa Ngo; Minh Vuong Ngo; Trong Thuong Huynh; Cong Hieu Nguyen; Thi Minh Chau Le (My University, 2025)
Developing Experimental Scenarios to Evaluate Dynamic Response Effectiveness of DFIG-Based Wind Power Generator
Keywords: DFIG; Wind power generator; Dynamic response